HUBUNGAN ANTARA BAHASA DENGAN LOGIKA DAN MATEMATIKA MENURUT PEMIKIRAN WITTGENSTEIN - Hardi Suyitno (Humaniora, 2008)
The aim of this study is to find out the relation between language with logic and mathematics. This study is essential because language, logics, and mathematics are important for developing science and technology. Existence of a nation depend on its competence on science and technology. Wittgenstein is a prominent philosopher in twenteeth century, especially on language analyses. He is the person who masters modern logic in his era. He exerted more of his time for mathematics, especially since 1929 until 1944. According to Wittgenstein, language is the basix of logic and mathematics. The implication of his account is mastering in language is a prerequisities for mastering in logic and mathematics. The suggestion is education practice ought to develop the language education, logic education, and mathematics education in integrity.